BLENDED LEARNING STRATEGY: ALTERNATIF PEMBELAJARAN TOEFL BAGI GURU-GURU MGMP NON-BAHASA INGGRIS - Santiana Santiana; Ratu Sarah Pujasari; Asri Siti Fatimah (Jurnal Inovasi Pengabdian Masyarakat Pendidikan, 2021)
The importance of English proficiency for non-English MGMP teachers cannot be overstated. In order to receive an appropriate score for further studies or other reasons, they must be able to answer the Test of English as a Foreign Language (TOEFL) questions correctly and properly. One of the challenges for Non-English MGMP teachers in answering TOEFL questions is that they do not know the format of the questions in the exam, as well as the time constraints to learn about TOEFL because most of them are already busy with their daily work, namely teaching. Based on current issues, the use of suitable Learning Media is a solution for learning TOEFL with the assistance of teachers who can direct them to learn effectively and efficiently. To address these issues, the Blended Learning TOEFL implementation is the best approach for learning TOEFL for Non-English MGMP Teachers. This is accomplished by integrating face-to-face and online learning methods.